Sovereign spreads and corporate taxation - Hayley Pallan (Graduate Institute of International and Development Studies, 2022)
Do sovereign bond investors care about taxation in the countries where they invest? In this paper, I examine the response of sovereign spreads to changes in tax revenues, bases and rates. In simple OLS regressions there is a negligible relationship between sovereign spreads and taxation. However, there are stronger relationships in emerging markets, specifically for corporate taxation. There is a particularly important role of corporate tax base changes in emerging markets for sovereign spreads - this contemporaneous relationship holds using both annual and daily datasets. Additionally, an assessment of how sovereign spreads respond to tax changes under various fiscal environments highlights the role of initial fiscal space in how sovereign spreads respond to aspects of corporate taxation. Finally, I estimate local projections in order to assess the dynamic response of sovereign spreads to corporate taxation. These results are consistent with the finding that corporate tax base expansion (rather than corporate tax rate hikes) are associated with lower borrowing costs for governments in fiscal precarity - most strongly for countries with low levels of fiscal space in the medium term.
Keywords: E62; H87; H63; 330; Sovereign Spreads; Fiscal Space; Corporate Tax Reform